Basic Concepts in Physiologically Based Pharmacokinetic Modeling in Drug Discovery and Development. (14th August 2013) - Jones, HM; Rowland‐Yeo, K
Abstract : The aim of this tutorial is to introduce the concept of physiologically based pharmacokinetic (PBPK) modeling to individuals in the pharmaceutical industry who may be relatively new to this area and to demonstrate application of this approach in a preclinical and clinical setting. The tutorial provides some background on PBPK models and their data requirements, introduces strategies for PBPK modeling in drug development, and includes a discussion on regulatory considerations and potential resource issues. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e63; doi:10.1038/psp.2013.41 ; published online 14 August 2013